1,5-Bis[(E)-1-(2-hydroxyphenyl)ethylidene]thiocarbonohydrazide monohydrate - Fasihuddin B, Ahmad; Md Abu, Affan; Dayang NA, Chee; Edward RT, Tiekink (International Union of Crystallography, 2010)
In the title compound, C17H18N4O2S·H2O, the thiourea derivative is almost planar, with an r.m.s. deviation for the non-H atoms of 0.057 Å. The hydroxyl groups lie to the same side of the molecule as the thione S atom, a conformation that allows the formation of intramolecular O-H...S and O-H...N hydrogen bonds. In the crystal structure, the thiourea and water molecules self-assemble into a two-dimensional array by a combination of Owater-H...Ohydroxyl, N-H...Owater and Owater-H...S hydrogen bonds and C-H...[pi] interactions.